Improving The Efficiency of Ups Performance in Depok City - Lokahita, Baskoro; Effendi, Aisyia Prasetya; Firdaus, Hana Syarifah; Wahyuningsih, Ni Putu Sri (Journal Research of Social Science, Economics, and Management, 2025)
The problem of waste in urban areas such as Depok City requires effective and efficient management solutions to reduce the burden on the final processing site (TPA). The Waste Management Unit (UPS) is one of the strategies of the Depok City Government in handling region-based domestic waste. This study aims to evaluate the technical performance of UPS operating in several locations in Depok City, as well as identify potential for improvement in processing efficiency. The mixed-methods approach is used through the collection of primary and secondary data. Quantitatively, load count analysis and daily mass balance were carried out to analyze the flow of material from input to compost output. Qualitatively, direct observation, semi-structural interviews, and work system studies were carried out. Case studies on three UPS (Jalan Jawa, Sukatani, and Merdeka 1) showed that the proportion of organic waste dominated (more than 94%) with a decrease in mass of up to 74% after the composting process. Nevertheless, the efficiency of the process varies depending on the sorting mechanism, available equipment, and human resource capacity. The results of the analysis show that UPS's performance has not been fully optimal in reducing the burden of waste to the landfill. This study recommends improving operational management, strengthening institutions, and integrating community roles to achieve a sustainable regional waste management system.